SUPPORTIVE CARE NEEDS PADA KELUARGA PASIEN STROKE DI KLINIK SYARAF BANJARMASIN, INDONESIA - Agianto; Setiawan, Herry (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Mortality and morbidity were caused by stroke. In ASEAN, stroke is the fourth leading andIndonesia is number one. South Kalimantan is the top four for high prevalence in Indonesia. Strokepatients require long-term care at their home and their quality of life will be good if they get theappropriate long-term care and support from caregivers. Quality of life of caregivers also need tobe considered. The purpose of study was to determine the supportive care needs of strokecaregivers when take care at home. A descriptive study used at neurological clinic, with 112caregivers, and using questionnaire. Data analysis used frequency distribution. The results showedthat the supportive care needs among stroke caregivers in the community is at a moderate level(100%, n = 112); with emotional domain (27.11 ± 8.47), psychosocial domain (26.84 ± 6.36),informational domain (23.74 ± 4.20), practice domain (16.3 ± 4.24), spiritual domain (6.43 ±1.30), and physical domain (3.06 ± 1.17). Nurses in the community need to improve the quality andthe health care system to help stroke caregivers in taking care for long term.